On the relationship between attacking third passes and success in the English Premier League - Myers, B. R.; Coughlin, B. Q. (The Sport Journal, 2016)
This research examined how changes in attacking third pass behavior can impact a team`s ability to maintain leads and secure wins based on data collected from the 2011-2012 English Premier League Season. A team`s attacking third behavior is measured by the number of attacking third passes completed per minute. The results of this paper suggest that while teams tend to complete less passes in the final third when they are ahead in a match vs. being behind, there is evidence to suggest that a drop in attacking third pass behavior when ahead in a match will reduce the likelihood of maintaining a lead and securing three points.